A method for preparing a gas separation membrane by ice crystal induced covalent crosslinking

CN122912688APending Publication Date: 2026-10-16SHANDONG BONA BIOLOGICAL TECH GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320111.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]目前的气体分离膜产品普遍存在受“Trade off效应”限制,分离性能难以同时兼顾高选择性与高渗透性,在高温、高压、强腐蚀等苛刻工业工况下易发生膜结构破损、性能衰减,使用寿命较短的问题,限制了其在高端气体分离场景中的应用

Benefits of technology

[0017]与现有技术相比,本发明的优点和积极效果在于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912688A_ABST
    Figure CN122912688A_ABST
Patent Text Reader

Abstract

The application belongs to the field of gas separation membranes, and proposes a method for preparing a gas separation membrane by ice crystal induction-covalent crosslinking, comprising the following steps: S1, preparing a two-dimensional nanosheet layer functional liquid; S2, ice crystal induction assembly: slowly pouring the two-dimensional nanosheet layer functional liquid along the inner wall of a pre-cooled mold, directional freezing and controlling the growth speed of ice crystals; S3, dynamic covalent crosslinking: quickly spraying a crosslinking agent on the surface of the ice crystals in the middle of growth, continuing to freeze until the ice crystals are completely generated and solidified; S4, membrane activation: removing the ice crystals by drying the ice crystals, obtaining a nascent gas separation membrane, activating by vacuum heating to a certain temperature, and naturally reducing to room temperature to obtain a gas separation membrane. The gas separation membrane prepared by the application has high gas permeation flux and high gas selectivity, and breaks through the limitation of the traditional Trade off effect; the introduced dynamic covalent crosslinking bond can repair the small defects caused by the membrane during use, thereby prolonging the service life of the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas separation membranes, and particularly relates to a method for preparing gas separation membranes by ice crystal-induced covalent crosslinking. Background Technology

[0002] Gas separation membrane technology, as a novel gas separation technology, has the advantages of small footprint, low energy consumption, and simple operation. It has been widely used in many key fields such as air separation, hydrogen purification, natural gas purification, and carbon capture, and has become one of the indispensable core technologies in modern industrial production.

[0003] Current gas separation membrane products are generally limited by the "trade-off effect," making it difficult to simultaneously achieve high selectivity and high permeability. They are also prone to membrane structure damage, performance degradation, and short service life under harsh industrial conditions such as high temperature, high pressure, and strong corrosion, which limits their application in high-end gas separation scenarios. Summary of the Invention

[0004] This invention addresses the technical problems existing in the gas separation membranes mentioned above by proposing a method for preparing gas separation membranes by ice crystal-induced covalent crosslinking. The separation membrane prepared by this method has both high gas selectivity and permeability, and can self-repair micro-damage, resulting in a long service life.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing a gas separation membrane by ice crystal induction-covalent crosslinking, comprising the following specific steps:

[0006] S1. Preparation of two-dimensional nanosheet functional liquid;

[0007] S2, Ice Crystal Induced Assembly: The mold is pre-cooled to a certain temperature on a cold table, and the two-dimensional nanosheet functional liquid prepared in S1 is slowly poured into the inner wall of the mold. Directional freezing is performed, and ice crystals begin to form. The temperature of the cold table is adjusted to control the growth rate of the ice crystals.

[0008] S3, Dynamic covalent crosslinking: A certain amount of terephthalaldehyde is added to anhydrous ethanol to prepare a terephthalaldehyde solution of a certain concentration, which is then placed in an atomizing bottle to prepare a crosslinking agent; during the middle stage of ice crystal growth, the crosslinking agent is quickly sprayed onto the surface of the ice crystal, and freezing continues until the ice crystal is completely formed and solidified;

[0009] S4. Membrane activation: Transfer the completely solidified ice crystals generated in S3 to a freeze dryer to dry and remove the ice crystals, and obtain the nascent gas separation membrane; transfer the nascent gas separation membrane to a vacuum oven and heat it to a certain temperature for activation, and then let it cool naturally to room temperature to obtain the finished gas separation membrane.

[0010] Preferably, step S1 specifically includes: adding two-dimensional nanosheet powder to deionized water to prepare a two-dimensional nanosheet solution with a certain solid content, ultrasonically dispersing for 30 min, centrifuging and taking the supernatant to obtain a two-dimensional nanosheet dispersion; adding a certain amount of polyethyleneimine to the two-dimensional nanosheet dispersion, stirring at room temperature for 30 min, adding a certain volume of tert-butanol and stirring to mix, and ultrasonically degassing for 10 min after uniform mixing to obtain a two-dimensional nanosheet functional liquid.

[0011] Preferably, the two-dimensional nanosheets include at least one of graphene oxide sheets, MXene nanosheets, and MOF nanosheets.

[0012] Preferably, in step S1, the solid content of the two-dimensional nanosheet solution is 0.1% to 10%; the amount of polyethyleneimine added is 1 to 10 wt% (relative to the mass of the two-dimensional nanosheet); and the volume ratio of tert-butanol to deionized water is (2:8) to (3:7).

[0013] Preferably, in step S2, the pre-cooling temperature is -18 to -22°C.

[0014] Preferably, in step S2, the ice crystal growth rate is controlled to be 5~10 μm / s.

[0015] Preferably, in step S3, the amount of terephthalaldehyde added is 2-5 wt% (relative to the mass of the two-dimensional nanosheets), and the concentration of the terephthalaldehyde solution is 0.5-2 mg / mL.

[0016] Preferably, in step S4, the heating temperature is 100~120℃ and the activation time is 2~6h.

[0017] Compared with the prior art, the advantages and positive effects of the present invention are as follows:

[0018] 1. The present invention provides a method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking. The gas separation membrane prepared by this method has nanosheet vertical channels. Under the action of these vertical channels, both high gas permeation flux and high gas selectivity are taken into account, breaking through the limitations of the traditional trade-off effect. At the same time, the introduced dynamic covalent crosslinking bonds can repair the minor defects caused by the membrane during use, thereby extending the actual service life of the membrane. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 Charts showing the physical properties of the gas separation membranes prepared in Examples 1-7 before and after damage repair;

[0021] Figure 2 The following are schematic diagrams illustrating the CO2 / CH4 selection of the gas separation membranes prepared in Examples 1-7. Detailed Implementation

[0022] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.

[0023] Numerous specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways than those described herein, and therefore the invention is not limited to the specific embodiments disclosed in the following specification. Example 1

[0024] S1. Preparation of two-dimensional nanosheet functional liquid: MXene sheet powder was added to deionized water to prepare a two-dimensional nanosheet solution with a solid content of 0.5%. The solution was ultrasonically dispersed for 30 min, and the supernatant was collected after centrifugation to obtain the two-dimensional nanosheet dispersion. Polyethyleneimine (PEI) of 3% by weight of MXene sheet powder was added to the two-dimensional nanosheet dispersion and stirred at room temperature for 30 min. Tert-butanol was added and gently stirred to mix, controlling the volume ratio of tert-butanol to water to be 3:7. After mixing evenly, ultrasonic degassing was performed for 10 min. The ultrasonic operation is used for peeling dispersion and degassing. It is a high-energy process and should be used for short periods. It cannot replace gentle stirring after the addition of tert-butanol to avoid shearing the MXene sheets. Gentle stirring after adding tert-butanol helps to achieve macroscopic mixing of PEI, tert-butanol and MXene sheet solution, with gentle mass transfer, low shear, protection of sheets, prevention of sheet flocculation and agglomeration, and reduction of air entrapment.

[0025] S2, Ice crystal induced assembly: The mold is pre-cooled to -20℃ on a cold table, and the prepared two-dimensional nanosheet functional liquid is slowly poured into the inner wall of the mold to start directional freezing, so that ice crystals begin to form. The temperature of the cold table is adjusted to precisely control the growth rate of the ice crystals to 5um / s.

[0026] S3. Dynamic Covalent Crosslinking: 2% (by weight) of terephthalaldehyde (by mass) of MXene sheet powder is added to anhydrous ethanol to prepare a 0.5 mg / mL covalent crosslinking agent, which is then placed in an atomizing bottle. During the middle stage of ice crystal growth, the covalent crosslinking agent is rapidly sprayed onto the ice crystal surface, and freezing continues until the ice crystals are completely formed and solidified. Since the crosslinking agent preferentially accumulates at the MXene sheet interface, interfacial crosslinking between sheets is achieved. Because the ice crystal framework is already fixed, crosslinking does not interfere with ice crystal orientation, preserving the continuous mass transfer channels constructed by the ice template. A thin liquid phase still exists in the gaps, allowing crosslinking molecules to diffuse to all MXene interfaces, resulting in uniform crosslinking and reduced membrane defects. The ice crystal growth window is very short, and the duration of steady-state growth in the middle stage is limited. Rapid, one-time atomization coverage ensures uniform crosslinking agent concentration across the entire membrane surface. Rapid spraying followed by continued freezing quickly freezes and locks the crosslinking system, avoiding macroporous defects and non-selective leakage channels caused by phase separation.

[0027] S4. Membrane Activation: The completely solidified ice crystals are transferred to a freeze dryer to remove the ice crystals, while retaining the three-dimensional interconnected channels / interlayer channels constructed by the ice crystals, resulting in a nascent gas separation membrane with a shaped but not yet fully stable structure. The nascent gas separation membrane is then transferred to a vacuum oven and heated to 120°C for 4 hours for activation. This process thoroughly removes residual solvents and bound water, promotes the solidification of the PEI and MXene interface, precisely controls and locks the two-dimensional interlayer sieving channels, and simultaneously inhibits MXene oxidation, improving membrane mechanics and long-term operational stability, resulting in the finished gas separation membrane.

[0028] Performance Testing: (I) Using a BONA-GS-17 gas permeation testing device, the permeation fluxes of CO2 and CH4 were measured at 25℃ and 0.1 MPa, and the CO2 / CH4 selectivity was calculated. (II) Controllable micro-damage was created to the membrane using a blade scratch method. After heating at 80℃ for 24 hours, the permeation fluxes of CO2 and CH4 were measured at 25℃ and 0.1 MPa, and the CO2 / CH4 selectivity was calculated.

[0029] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 1610 GPU and a CO2 / CH4 selectivity of 169. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 1288 GPU and the CO2 / CH4 selectivity is 144. Example 2

[0030] Except for the solid content of the MXene sheet solution in step S1 being 1%, the other operations are the same as in Example 1.

[0031] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 1421 GPU and a CO2 / CH4 selectivity of 178. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 1151 GPU and the CO2 / CH4 selectivity is 150. Example 3

[0032] Except for the solid content of the MXene sheet solution in step S1 being 2%, the other operations are the same as in Example 1.

[0033] Before damage, the CO2 permeation flux of the gas separation membrane prepared in this embodiment was 1065 GPU, and the CO2 / CH4 selectivity was 201. After membrane damage repair, the CO2 permeation flux of the gas separation membrane was 873 GPU, and the CO2 / CH4 selectivity was 160. Example 4

[0034] Except for controlling the growth rate of ice crystals to 8 μm / s in step S2, the other operations are the same as in Example 1.

[0035] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 1401 GPU and a CO2 / CH4 selectivity of 174. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 1121 GPU and the CO2 / CH4 selectivity is 143. Example 5

[0036] Except for controlling the growth rate of ice crystals to 10 μm / s in step S2, the other operations are the same as in Example 1.

[0037] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 1311 GPU and a CO2 / CH4 selectivity of 171. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 1049 GPU and the CO2 / CH4 selectivity is 137. Example 6

[0038] Except that the mass-volume concentration of the covalent crosslinking agent in S3 is 1 mg / mL, the other operations are the same as in Example 1.

[0039] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 1310 GPU and a CO2 / CH4 selectivity of 181. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 1050 GPU and the CO2 / CH4 selectivity is 145. Example 7

[0040] Except that the mass-volume concentration of the covalent crosslinking agent in S3 is 2 mg / mL, the other operations are the same as in Example 1.

[0041] The gas separation membrane prepared in this embodiment has a CO2 permeation flux of 908 GPU and a CO2 / CH4 selectivity of 201. After membrane damage repair, the CO2 permeation flux of the gas separation membrane is 727 GPU and the CO2 / CH4 selectivity is 161.

[0042] like Figure 1 and Figure 2 As shown in Examples 1-3, as the solid content of the two-dimensional nanosheet solution increases, the membrane structure gradually becomes denser, the vertical pores gradually shrink, the CO2 permeation flux decreases, but the selectivity increases.

[0043] In Examples 4 and 5, as the ice crystal growth rate increases, dendritic ice crystals are easily generated, causing the vertical channels to gradually become bent and disordered, and the gas flux to decrease slightly. Considering both permeation flux and selectivity, the ice crystal growth rate in Example 1 is preferably 5 μm / s.

[0044] In Examples 6 and 7, as the concentration of the crosslinking agent increases, the crosslinking density increases accordingly, the mechanical strength of the membrane increases, the spacing of the vertical channels gradually decreases, the gas selectivity increases, and the permeation flux decreases.

[0045] In Examples 1-7, after the gas separation membrane suffers minor damage, a large number of active end groups are exposed on the fracture surface. The dynamic bonds undergo reversible dissociation under service conditions, and the polymer chain segments gain fluidity. The molecular chains and free cross-linked small molecules on both sides of the crack migrate to the gap, contact each other, and wet the interface, physically filling the micropores / cracks. The active groups exposed on the fracture surface undergo dynamic exchange reactions, and dynamic covalent cross-links are regenerated at the crack interface, reconnecting the membrane substrates on both sides, rebuilding the complete cross-linked network, and closing the micro-defects. The gas sieving channels and interlayer mass transfer channels that were originally damaged by the cracks become continuous again, and the gas permeation flux and selectivity recover. Therefore, the intervention of the dynamic covalent cross-linking system can self-repair the damaged parts, and the gas selectivity and permeability can be restored to about 80% of the original performance, which can effectively extend the service life of the separation membrane. At the same time, the gas separation membranes prepared by this invention all have both high gas flux and high gas selectivity, and have broad application prospects in the field of gas separation.

[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking, characterized in that, The specific steps include the following: S1. Preparation of two-dimensional nanosheet functional liquid; S2, Ice Crystal Induced Assembly: The mold is pre-cooled to a certain temperature on a cold table, and the two-dimensional nanosheet functional liquid prepared in S1 is slowly poured into the inner wall of the mold. Directional freezing is performed, and ice crystals begin to form. The temperature of the cold table is adjusted to control the growth rate of the ice crystals. S3, Dynamic covalent crosslinking: A certain amount of terephthalaldehyde is added to anhydrous ethanol to prepare a terephthalaldehyde solution of a certain concentration, which is then placed in an atomizing bottle to prepare a crosslinking agent; during the middle stage of ice crystal growth, the crosslinking agent is quickly sprayed onto the surface of the ice crystal, and freezing continues until the ice crystal is completely formed and solidified; S4. Membrane activation: Transfer the completely solidified ice crystals generated in S3 to a freeze dryer to dry and remove the ice crystals, and obtain the nascent gas separation membrane; transfer the nascent gas separation membrane to a vacuum oven and heat it to a certain temperature for activation, and then let it cool naturally to room temperature to obtain the finished gas separation membrane.

2. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 1, characterized in that, Step S1 specifically includes: adding two-dimensional nanosheet powder to deionized water to prepare a two-dimensional nanosheet solution with a certain solid content, ultrasonically dispersing for 30 min, centrifuging and taking the supernatant to obtain a two-dimensional nanosheet dispersion; adding a certain amount of polyethyleneimine to the two-dimensional nanosheet dispersion, stirring at room temperature for 30 min, adding a certain volume of tert-butanol and stirring to mix, and ultrasonically degassing for 10 min after uniform mixing to obtain a two-dimensional nanosheet functional liquid.

3. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 2, characterized in that, Two-dimensional nanosheets include at least one of graphene oxide sheets, MXene nanosheets, and MOF nanosheets.

4. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 3, characterized in that, In step S1, the solid content of the two-dimensional nanosheet solution is 0.1% to 10%; the amount of polyethyleneimine added is 1 to 10 wt% of the mass of the two-dimensional nanosheets; and the volume ratio of tert-butanol to deionized water is (2:8) to (3:7).

5. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 4, characterized in that, In step S2, the pre-cooling temperature is -18 to -22°C.

6. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 5, characterized in that, In step S2, the ice crystal growth rate is controlled to be 5~10 μm / s.

7. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 6, characterized in that, In step S3, the amount of terephthalaldehyde added is 2-5 wt% of the mass of the two-dimensional nanosheets, and the concentration of the terephthalaldehyde solution is 0.5-2 mg / mL.

8. The method for preparing a gas separation membrane by ice crystal-induced covalent crosslinking according to claim 7, characterized in that, In step S4, the heating temperature is 100~120℃ and the activation time is 2~6h.